Security : a multidisciplinary normative approach - Bailliet, Cecilia (International humanitarian law series, 2009)
Security is an all-encompassing term of art which is subject to diverse interpretations and understandings. It includes notions of protection against transnational threats, including terrorism, inter- and intra-state conflict, nuclear proliferation, forced migration, violation of womena (TM)s rights, climate change, etc. The papers in this collection provide fresh voices in the security debate, uniting scholars from different fields of law and philosophy to address normative gaps in interpretation, evolution and application. Part I considers calls for an expanded mandate for the UN Security Co.